Heritage education : turning myth into reality - the UMK experience - Farok Zakaria; Ab. Aziz Shuaib; Nasirin Abdillah (2010)
Heritage has been seen as a very important element in the development of a nation. Heritage on the other hand is dying and needs to be revived. There is a push to educate younger generation on the issue of dying heritage by creating awareness and appreciation towards heritage through education.All across the globe, there is a growing concern for the need to restore heritage into our education systems simply because haritage depicts one's identity of race and culture. In light of the above dilemma, Universiti Malaysia Kelantan (UMK) views haritage as an oppportunity that needs to be grabbed and properly utilized. Heritage to UMK is like a precious gem that neeeds to be given a new touch. Hence in July 2007,UMK introduced a unique academic programme named Bachelor of Heritage Studies with Honours to the Malaysian high school leavers. This paper will introduce the programme and the academic components, discuss problems related to the running of an academic heritage programme at tertiary levels and forecast the future of this programme